2010
DOI: 10.3395/reciis.v4i1.349pt
|View full text |Cite
|
Sign up to set email alerts
|

Violência no trabalho em saúde: um tema para a cooperação internacional em recursos humanos para a saúde

Abstract: Entre os temas dos recursos humanos em saúde vêm recebendo maior atenção as condições de trabalho e os riscos para a saúde dos trabalhadores, dentre os quais, de acordo com o Relatório Mundial da Saúde de 2006, consta a violência no trabalho. A partir do estudo da literatura e de documentos oficiais, o presente artigo procura evidenciar a relevância do problema e identificar elementos para elaboração de estratégias de cooperação internacional nesse tema. Estudos mostram que as agressões podem ultrapassar larga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
22

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 7 publications
1
4
0
22
Order By: Relevance
“…However, we found no studies to confirm the data from this research on the prevalence of occupational accidents among workers exposed to violence, but it is understood that accidents are representations of emotional and cognitive impairments brought about by the experience of violence. Workplace violence was associated with worker's absences, complementing findings in the literature that indicate this phenomenon as the cause of absence (3,9) . However, we note that in addition to the underreporting of violence in health services (8) , it has not been registered as cause of removal, which may result in the same occurring in health services.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, we found no studies to confirm the data from this research on the prevalence of occupational accidents among workers exposed to violence, but it is understood that accidents are representations of emotional and cognitive impairments brought about by the experience of violence. Workplace violence was associated with worker's absences, complementing findings in the literature that indicate this phenomenon as the cause of absence (3,9) . However, we note that in addition to the underreporting of violence in health services (8) , it has not been registered as cause of removal, which may result in the same occurring in health services.…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, violence at work has gained international prominence in discussions on the challenges related to human resources for health (3)(4)(5) . Prevalence rates show that the problem of violence in health services range from 17 to 94%, and frequently exceeds 50% of workers (2)(3)(4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissatisfaction with work had several effects on these individuals' organizational life, as well as on their physical and mental health. (14) Regarding health problems obtained in this documentary research, 297 records of medical leaves of absence between 2010-2012 were found, which involved 64.41% of the psychiatric hospital's health professionals and resulted in 4,671 days of absences (working days lost). These results are worrisome, for more than half of the workers were ill during this three-year period, resulting in losses for workers, institution and patients.…”
Section: Discussionmentioning
confidence: 99%
“…No Rio de Janeiro-RJ, 70,4% dos trabalhadores das Unidades Locais de Saúde foram vítimas de algum tipo de violência, como agressões verbais (65,5%), bulling (20%), agressões físicas (7,3%), assédio sexual (3,6%) e por discriminação racial (3,6%) (7) . Índices semelhantes foram verificados em Belo Horizonte-MG, com 68,9% de ocorrências contra os médicos (2) .…”
unclassified